Paparan Selektif Penggunaan Fitur Senyap dan Teman Dekat pada Twitter dan Instagram - Rahmiputri, Aisha Andari; Irwansyah, Irwansyah (Jurnal Studi Komunikasi, 2019)
Social media has become a part of human’s life. Social Networking Sites or SNS which a part of social media allows the users to create their own network. Not only that but users can also choose their friends, what kind of content they want to see, what kind of relationship then want to have, or to keep certain content just for a few people to see through social media. A few features like mute feature to close friends feature are there for users to use on Twitter and Instagram. This research will try to find out how those features are being used by the users and why those features are needed. In depth interview is used to six informants who use the mute and close friend feature on Twitter or Instagram. Selective exposure theory is used to see how someone is more interested in seeing contents that match their believes and interests. It shows that mute feature is used to filter some stuff that they want to see and avoid things they don’t like. The mute feature also useful for keeping the relationship in a good term between the users and other people. Meanwhile, close friends feature is used to maintain the connection users have with a few people where they can share stuff to those people only. Users also think that close friends feature is useful to protect their privacy.